EXENATIDE INDUCED ACUTE KIDNEY INJURY - Aijazi, Ishma; Abdulla, Fadhil M; Zuberi, Beyla J; Elhassan, Ahmed (Journal of Ayub Medical College Abbottabad, 2014)
Exenatide is an incretin mimetic. It was approved by the federal drug authority in 2005 for the treatment of type-2 diabetes. Since it is a relatively new medicine clinicians have limited experience with regards to its side effects and safety profile. We report a 47 year old lady who presented with exenatide associated acute kidney injury. She had type-2 diabetes for 10 years with mild micro albuminuria and normal renal functions. She was also taking a stable dose of metformin, gliclazide, angiotensin converting enzyme inhibitor and diuretic for over a year and there was no history of any recent use of non-steroid anti-inflammatory medications. One week after starting exenatide, she developed severe vomiting, followed by hypotension. She presented with acute renal insufficiency and severe lactic acidosis and had to be dialyzed on emergency basis. To our knowledge this is probably the first case reported in the local United Arab Emirate (U.A.E) population. Keywords: Exenatide, renal failure, incretin mimetics, complication